“Surgical Site Infections” and it’s Management ‘Our Experience’ at KMC/Civil Hospital Khairpur (Medical Forum Monthly, 2024)
Objective: To find out the incidence, causative organism, severity and treatment of surgical site infections (SSIs) at of KMC/Civil Hospital Khairpur Mir’s.Study Design: Prospective Observational study.Place and Duration of Study: This study was conducted at the in Surgical Unit and Gynae Obs, KMC/Civil Hospital Khairpur Mir’s from January 2018 to December 2018.Materials and Methods: The study included 100 patients in this study. Four of these patients were lost during follow up, therefore net 96 patients were statistically analyzed. 54 (56.25%) patient were male and 42 (43.75%) patients were female. All those post-operative cases were included in this study, who developed wound infection during their hospital stay or one month follow up. Protocol of pus culture and sensitivity report of each infected case was also followed in this study.Results: Out of 802 procedures, 96 (11.97%) patients developed SSIs. Mean age of these patients was 32.0 +7 years. Forty one patients (42.70%) were having different comorbidities. SSI was found more common in laparotomy, Pyelolithotomy, prostectomy and appendicectomy, accounting (68%) of overall recorded infections.In this study overall Gram-positive organism were (54%) and Gram-negative organism (46%).Conclusion: Surgical site infection (SSI) is common in developing countries, pre-operative assessment, aseptic measures and prophylactic antibiotic can reduce post-operative wound complications /sepsis. In this study, Piperacillin/Tazobactam found most effective and Oxytetracycline most resistant agents against these isolated organisms.